2022
DOI: 10.3389/fonc.2021.799759
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of a Prognostic Index Based on Genes Participating in Autophagy in Patients With Lung Adenocarcinoma

Abstract: BackgroundLung adenocarcinoma (LUAD) is a deadly respiratory system malignancy with poor prognosis. Autophagy is essential for the beginning, development, and therapy resistance of cancer. However, the expression of genes participating in autophagy in LUAD and their associations with prognosis remain unclear.MethodsPredictive genes participating in autophagy in LUAD samples from The Cancer Genome Atlas (TCGA) and Gene Expression Omnibus (GEO) datasets were investigated. TCGA and GEO cohorts were divided into t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 30 publications
1
10
0
Order By: Relevance
“…Additionally, a redox-related gene signature has been established in LUAD ( Xiao et al, 2022b ), which is only suitable for a subset of patients with NSCLC and also lacks reliable experimental verification. In the present study, the redox-related gene signature was first constructed in all the patients with NSCLC, and Kaplan–Meier survival curve showed that the high-risk group had a worse OS than the low-risk group, which was different from and cannot be replaced by the previously constructed signature using hypoxia-related gene ( Chen et al, 2022 ), pyroptosis-related gene ( Zhang and Yan, 2021 ; Li et al, 2022 ), autophagy-related gene ( Wu et al, 2021a ), and inflammatory response-related gene ( Zou et al, 2021 ) because it could be meaningful in exploring the value of the redox-related gene in initiation, progression, prognosis, and therapy of NSCLC. The previous prognostic signatures in other cancers showed better diagnostic performance, with an AUC value of more than 0.8 ( Qian et al, 2022 ; Zhang et al, 2022 ).…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…Additionally, a redox-related gene signature has been established in LUAD ( Xiao et al, 2022b ), which is only suitable for a subset of patients with NSCLC and also lacks reliable experimental verification. In the present study, the redox-related gene signature was first constructed in all the patients with NSCLC, and Kaplan–Meier survival curve showed that the high-risk group had a worse OS than the low-risk group, which was different from and cannot be replaced by the previously constructed signature using hypoxia-related gene ( Chen et al, 2022 ), pyroptosis-related gene ( Zhang and Yan, 2021 ; Li et al, 2022 ), autophagy-related gene ( Wu et al, 2021a ), and inflammatory response-related gene ( Zou et al, 2021 ) because it could be meaningful in exploring the value of the redox-related gene in initiation, progression, prognosis, and therapy of NSCLC. The previous prognostic signatures in other cancers showed better diagnostic performance, with an AUC value of more than 0.8 ( Qian et al, 2022 ; Zhang et al, 2022 ).…”
Section: Discussionmentioning
confidence: 88%
“…However, in the current study, the AUC value for OS at the 5 year periods was 0.657 in TCGA and 0.717 in GSE31210. Various researches showed that the AUC values of many signatures for lung cancer or NSCLC were more than 0.75 ( Wu et al, 2021a ; Li et al, 2021b ; Ouyang et al, 2021 ; Qu et al, 2021 ; Zhang and Yan, 2021 ; Zou et al, 2021 ; Wang et al, 2022b ; Chen et al, 2022 ; Li et al, 2022 ; Yang et al, 2022 ). Thus, the prognostic biomarkers or signatures with a higher AUC value need to be explored in the future.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We rstly revealed that AMDHD1 was highly expressed in LUAD and its overexpression was correlated with patients' poor outcome. GAPDH was found to be one of ve key genes related to prognosis and CD8 + T-cell in ltration in LUAD [22,23]. Moreover, Sakthidhasan et al [24] con rmed the apoptotic and anti-proliferative potential of GAPDH against human lung carcinoma.…”
Section: Discussionmentioning
confidence: 98%